2001
DOI: 10.1159/000052942
|View full text |Cite
|
Sign up to set email alerts
|

Is the Zona pellucida Thickness of Metaphase-II Oocytes in an IVF/ICSI Program Influenced by the Patient’s Age?

Abstract: Zona pellucida (Z.p.) thickness is believed to be considerably influenced by hormonal stimulation. Assessments of the influence of the patient’s age on Z.p. thickness have been at variance. In our study we wanted to investigate, among several other parameters, the age of the patient as a possible factor influencing Z.p. thickness. Prior to intracytoplasmatic sperm injection (ICSI) we determined the mean thickness of the Z.p. of 843 metaphase-II oocytes from 100 patients, which had been obtained after ovarian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…Some studies have suggested positive correlation between ZPT and age [26,30] Our results, on the contrary, showed that there is a significant inverse correlation between ZPT and women's age, between 24 and 46 years. The reduction of ZPT can be attributed to a progressive decrease of the capability of oocytes and granulosa cells to synthesize and properly assemble ZP proteins.…”
Section: Discussioncontrasting
confidence: 93%
“…Some studies have suggested positive correlation between ZPT and age [26,30] Our results, on the contrary, showed that there is a significant inverse correlation between ZPT and women's age, between 24 and 46 years. The reduction of ZPT can be attributed to a progressive decrease of the capability of oocytes and granulosa cells to synthesize and properly assemble ZP proteins.…”
Section: Discussioncontrasting
confidence: 93%
“…Moreover, a compaction of inner part of ZP was seen in RA+IvA oocytes, probably related to the abovementioned altered CG release. A thickened ZP may impair IVF procedures influencing sperm penetration, and it was related to lower fertilization rate of older patients [74]. Even if ICSI may overcome this problem, we must highlight that ZP thickening may also impair early embryo development, limiting metabolic exchanges between the embryo and the surrounding microenvironment [73].…”
Section: Zona Pellucidamentioning
confidence: 99%
“…There is controversy in the literature regarding this aspect, as some studies suggest a significant increase in ZPt with age [74,75] whereas others have shown the contrary [76]. All this data were obtained by light microscopy that cannot be efficient in revealing fine variations in thickness.…”
Section: Zona Pellucidamentioning
confidence: 99%
“…Any intrinsic or extrinsic factors that disturb these events may cause lack of fertilization and decrease embryo viability, leading to infertility (8,10). It has been reported that the ZPT is influenced by various factors, including maternal age (13,(15)(16)(17)(18), elevated basal FSH concentrations (19), cause of infertility, and ovarian hormonal stimulation in ART cycles (19,20). In addition, both suboptimal in vitro culture conditions and embryo cryopreservation may adversely affect the thickness and hardness of the ZP, and they may interfere with the secretion of trophectodermderived ZP lysin, which promotes ZP thinning and embryo hatching (10,21).…”
mentioning
confidence: 99%